2019
DOI: 10.2174/1874473712666190114141157
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Risky Sexual Behaviors, and HIV in Nigeria: A Meta-Analytic Review

Abstract: Background: Alcohol consumption is associated with risky sex, which increases the risk of acquiring and transmitting HIV. Objective: To examine the prevalence of, and associations among alcohol, risky sex, and HIV, in Nigeria. Methods: We searched electronic databases and reviewed reference sections of relevant papers to locate studies that sampled people living in Nigeria and assessed both alcohol and sexual risk behavior. We calculated effect sizes to determine (a) prevalence of alcohol and sex behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…The association between alcohol and unsafe sex has been observed among American college students [30]. A meta-analysis study has reported, people who consume alcohol had significantly multiple partners, sex without a condom or inconsistent use of condoms [31].…”
Section: Discussionmentioning
confidence: 99%
“…The association between alcohol and unsafe sex has been observed among American college students [30]. A meta-analysis study has reported, people who consume alcohol had significantly multiple partners, sex without a condom or inconsistent use of condoms [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to some research, only very high levels of alcohol intake reduce the probability of condom use [30]. On the contrary, all known studies performed in less developed or recently industrialized parts of the world confirmed the association of the alcohol intake with the non-use of condoms and other risky sexual behaviors [55][56][57][58][59][60][61][62]. It can be reasonably assumed that the social progress correlates with improvements of morality, so that distracting factors such as alcohol lose their significance.…”
Section: Discussionmentioning
confidence: 99%
“…The association between alcohol and unsafe sex has been observed among American college students [31]. A meta-analysis study has reported, people who consume alcohol had signi cantly multiple partners, sex without a condom or inconsistent use of condoms [32].…”
Section: Discussionmentioning
confidence: 99%